2001
DOI: 10.1002/1522-2640(200106)73:6<658::aid-cite6583333>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Operating Conditions for a Transpiring Wall Reactor for Supercritical Water Oxidation

Abstract: The synthesis of diethylacetal from ethanol and acetaldehyde catalysed by the acid resin Amberlyst 18 (Rohm and Haas) is considered. The adsorption and reaction experiments were performed in a laboratory scale fixed bed adsorptive reactor, operating isothermally at 15 C and at atmospheric pressure. The experimental results of dynamic adsorption of binary non-reactive mixtures are reported and used to obtain multicomponent adsorption equilibrium isotherms Langmuir type. The reaction kinetics reported in a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…In the literature, two methodologies have been utilized: 1) modeling turbulent mixing in the absence of phase boundaries [5][6][7][8][9][10][11][12][13], and 2) microscale modeling of individual droplets immersed in supercritical or near-critical fluids [1,2,[14][15][16][17][18][19][20][21][22]. The former applies only to fully miscible conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, two methodologies have been utilized: 1) modeling turbulent mixing in the absence of phase boundaries [5][6][7][8][9][10][11][12][13], and 2) microscale modeling of individual droplets immersed in supercritical or near-critical fluids [1,2,[14][15][16][17][18][19][20][21][22]. The former applies only to fully miscible conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies [1,2,5,7,[9][10][11][12][13][18][19][20][21] used the ideal fluid model in computing the diffusive driving force, although the equation of state, thermodynamic and transport properties, etc., took account of the non-ideality in these studies. On the other hand, the following numerical studies used the non-ideal driving force for SCF mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Most commercial and industrial applications require that engineering designs and materials overcome corrosion and plugging problems and that systems operate on a continuous duty cycle (Azadi et al, 2011;Elliott, 2008;Guo et al, 2007). Some common, SCW-reactor considerations are presented here, while extensive and detailed reviews can be found elsewhere (Bermejo et al, 2005a(Bermejo et al, , 2005b(Bermejo et al, , 2009Calzavara et al, 2004;Fauvel et al, 2003Fauvel et al, , 2005Lieball et al, 2001;Machida et al, 2011;Marrone & Hong, 2009;Mitton et al, 2000;Peter, 2004;Tan et al, 2011;Veriansyah et al, 2009;Wellig et al, 2005;Yoshida & Matsumura, 2009). …”
Section: Reactor Kinetics and Design Considerationsmentioning
confidence: 99%
“…Therefore, a novel tubular reactor type with a hydrothermal burner and transpiring-wall technology has been developed and investigated during the last few years [43][44][45][46][47][48].…”
Section: Previous Work In the Field Of Scwo At Eth Zurichmentioning
confidence: 99%
“…Therefore, temperature profiles were measured using special intermediate rings between the individual transpiring-wall elements. Finally, these experiments provided data for the validation of turbulent reactive computational fluid dynamic (CFD) models [44,46,48].…”
Section: Objectivesmentioning
confidence: 99%